Integration of Chinese and Javanese Ethnicities in Multicultural Life as a Manifestation of Historical and Cultural Harmonization in Surakarta - Setiawan, Johan (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research reviews the integration and interaction between ethnic Chinese and Javanese in the city of Surakarta, with a focus on various aspects of community life. The background includes strong symptoms related to ethnic problems after the 1998 reformation, especially in Surakarta, and reconciliation efforts to reduce increasingly strong ethnic symptoms. The aim of the research is to understand how interactions are formed between the two ethnic groups through education, language, economics, religion, community activities, arts, marriage, and culture. The method used is the historical method with heuristic, criticism, interpretation, and historiography stages. The research results show that there is a positive interaction between ethnic Chinese and Javanese in various aspects of life, creating harmony and integration in Surakarta's multicultural society. In conclusion, this interaction plays an important role in maintaining social harmony and cultural diversity in the city of Surakarta.